Influence of Quasiperiodic Gravitational Modulation on Convective Instability of Liquid-Liquid Polymerization Front. (20th December 2015) - Assiyad, Saadia; Allali, Karam; Belhaq, Mohamed
Abstract : The influence of quasiperiodic gravitational modulation on convective instability of polymerization front with liquid monomer and liquid polymer is studied. The model includes the heat equation, the concentration equation, and the Navier-Stokes equations under the Boussinesq approximation. The linear stability analysis of the problem is carried out and the interface problem is derived. Using numerical simulations, the convective instability threshold is determined and the boundary of the convective instability is obtained for different amplitudes and frequencies ratio.